How to read Nancy the elements of comics in three easy panels - Karasik, Paul 1956-; Newgarden, Mark (Fantagraphics Books, Inc., 2017)
"Everything that you need to know about reading, making, and understanding comics can be found in a single Nancy strip by Ernie Bushmiller from August 8, 1959. Paul Karasik and Mark Newgarden's groundbreaking work How to Read Nancy ingeniously isolates the separate building blocks of the language of comics through the deconstruction of a single strip. No other book on comics has taken such a simple yet methodical approach to laying bare how the comics medium really works. No other book of any kind has taken a single work by any artist and minutely (and entertainingly) pulled it apart like this. How to Read Nancy is a completely new approach towards deep-reading art. In addition, How to Read Nancy is a thoroughly researched history of how comics are made, from their creation at the drawing board to their ultimate destination at the bookstore. Textbook, art book, monogram, dissection, How to Read Nancy is a game changer in understanding how the "simplest" drawings grab us and never leave."--Amazon.com
Keywords: Bushmiller, Ernie / Nancy; Nancy (Bushmiller, Ernie); Nancy (Fictitious character : Bushmiller); Comic books, strips, etc; Graphic novels